Development of a Start Basic Engineering Manual (Bunch Start, Medium Start, Long Start) for Athletic Court Students - M., Benny Aprial; Sari, Ika Endah Puspita; Lubis, Ade Evriansyah; Helmi, Bobby; Aditya, Rinaldi (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
This study aims to help provide references aimed at athletic lecturers and students as well as the general public regarding basic technical materials (Bunch Start, Medium Start, Long Start) contained in the compulsory courses in every Health and Recreation Physical Education study program in the form of a technical manual. basic start. The method in this research uses the method of research and development or Research and Development (R & D). This research was conducted in several steps, namely: identification of potentials and problems, information gathering, product design, product manufacture, expert validation, product revision, testing, final production. The research subjects were in a small group of 10 people consisting of 1 trainer, 1 athletic lecturer and 8 students who took basic athletic skills courses and the field trials used 20 people consisting of 2 trainers, 2 lecturers and 16 STOK Bina Guna students. The data collection technique used in this study was an instrument in the form of an assessment sheet. The data analysis technique of this research is descriptive qualitative and quantitative descriptive. The result of the percentage of this research is the Media Expert of 94.44%, and the eligibility percentage of the Material Expert is 98.5%. Based on the small group trial, it was found that the percentage of calibration was 84.9% and the field trial was 89.85%. This medium is feasible.